Excitatory and inhibitory neuronal signaling in inflammatory and diabetic neuropathic pain - Ulrike Breitinger; Hans-Georg Breitinger (BMC, 2023)
Abstract Pain, although unpleasant, is an essential warning mechanism against injury and damage of the organism. An intricate network of specialised sensors and transmission systems contributes to reception, transmission and central sensitization of pain. Here, we briefly introduce some of the main aspects of pain signal transmission, including nociceptors and nociceptive signals, mechanisms of inflammatory and neuropathic pain, and the situation of diabetes-associated neuropathic pain. The role of glia-astrocytes, microglia, satellite glia cells-and their specific channels, transporters and signaling pathways is described. A focus is on the contribution of inhibitory synaptic signaling to nociception and a possible role of glycine receptors in glucose-mediated analgesia and treatment-induced diabetic neuropathy. Inhibitory receptors such as GABAA- and glycine receptors are important contributors to nociceptive signaling; their contribution to altered pain sensation in diabetes may be of clinical relevance, and they could be promising therapeutic targets towards the development of novel analgesics.